2017
DOI: 10.3126/jcmc.v7i3.23692
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge regarding sexual and reproductive health among adolescents in higher secondary school

Abstract: Background: Adolescent reproductive health is one of the component of the reproductive health. It is most important issue in the world. Reproductive capability is taking place at an earlier age and adolescents are indulging in risk taking behaviors day by day. The objective of this study is to assess knowledge regarding sexual and reproductive health among adolescents. Methods: A descriptive cross-sectional study was conducted in Kathmandu valley to assess the knowledge regarding sexual and reproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
(4 reference statements)
0
2
1
Order By: Relevance
“…A similar descriptive study was conducted in Wuhan, China among female college students showed that level of knowledge was statistically significant (P value < 0.001) between different sociodemographic variables. 9 This finding is contrast with the present study. As the studies were conducted in two different countries with different numbers of study population, such discrepancies of results could be explained.…”
Section: Discussioncontrasting
confidence: 99%
“…A similar descriptive study was conducted in Wuhan, China among female college students showed that level of knowledge was statistically significant (P value < 0.001) between different sociodemographic variables. 9 This finding is contrast with the present study. As the studies were conducted in two different countries with different numbers of study population, such discrepancies of results could be explained.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies showed that most youths know partially sexual and reproductive health (Shrestha & Awale, 2017;SPN, 2015;Upadhyaya, 2016;). Appropriate coordination between different governmental agencies and partners is necessary to disseminate information about youthfriendly sexual and reproductive health services; adolescents were not aware of sexual and reproductive health services provided for them (Khanal, 2016;WHO, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In 2017 Ministry of Health (MoH) launched the mobile app 'Khulduli' intending to promote sexual and reproductive health and right of adolescents in Nepal by empowering them with the right information about their health and helping them adopt a healthy lifestyle. Literature shows that some essential issues which are associated with access and utilization of youth-friendly sexual and reproductive health services are frequently occurring in Nepal, such as adequate knowledge of sexual and reproductive health services is poor among youth (Shrestha, 2017;Shrestha & Awale, 2017;WHO, 2017), Premarital sexual intercourse is common among young people (Puri & Celand, 2006), child marriage is still existing in Nepal (MoH, New ERA & ICF, 2017), and occurring complication of teenage pregnancy (Neupane, 2018). This review aims to assess the status of youth-friendly sexual and reproductive health services utilization in Nepal.…”
Section: Introductionmentioning
confidence: 99%